HUBUNGAN PARTUS LAMA DAN KETUBAN PECAH DINI DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD RADEN MATTAHER JAMBI - Hardiana Hardiana (MIDWIFERY HEALTH JOURNAL, 2019)
One cause of infant mortality is asphyxia, asphyxia is a condition where the baby immediately after birth does not breathe spontaneously and regularly. Based on data from Raden Mattaher General Hospital in Jambi Province in 2017 there were 107 cases of asphyxia and in 2018 the number of data on asphyxia patients increased to 116 cases. This study aims to determine the relationship of the old and amniotic early rupture with neonatorum asphyxiation in Raden Mattaher General Hospital Jambi Province in 2018. The study used a case control research method with a population of 116 respondents and control 116 respondents using random sampling technique. So the number of samples is 232 respondents. Data collection was done by filling out the checklist sheet carried out on March 27 with univariate and bivariate analysis. The results showed that the Old Partus group who experienced no Asphyxia were 42 infants (39.3%) and the Old Partus who had 65 Asphyxia (60.7%). This means that there is a relationship between the Old Partus and the Neonatorum Asphyxia with a p-value of 0.004 and OR 2.246. and those who did not experience premature rupture of amniotic neonatorum 65 infants (43.6%), and early rupture of membranes who experienced neonatorum asphyxia (38.6%). And there is a relationship between Early Ruptured Amniotic and Asphyxia Neonatorum with p-value 0.014 and OR 0.486. So there is a relationship between the Old Partus and the Amniotic Early Rupture with the occurrence of Neonatorum Asphyxia in Raden Mattaher General Hospital Jambi.